Developing a learning organization in the context of tourism and cultural related organizations in Kuching, Sarawak - Constance Rinen, Justin Wah (Universiti Malaysia Sarawak (UNIMAS), 2011)
Organizational initiatives to build a learning organization are inarguably important and trategic in the context of gaining and sustaining business competitive advantage. In this thesis, I repOlt a completed research work pertaining to understanding various organizational approaches towards developing a learning organization in the context of tourism and cultural related organizations in Kuching, Sarawa Firstly, this study examines the participated organizations and their approaches in creating a learning rganization. Secondly, it attempts to determine factors that can contribute towards effective learning in the context of employees of the tourism and cultural related organizations. Finally, this study identifies in what ways the participated organizations have engaged the use of leTs to promote a systematic organizationa} learning in the organization. In the research, I deployed both quafitative and quantitative methods to obtain data. An in-depth interview method was used to obtain qualitative data; a survey method was utilized to obtain descriptive data and also to test the proposed hypotheses relevant to this research. Overall, ten (10) organizations participated in this study. Out of this, eight (8) organizations participated in the interview. Questionnaires were distributed to all (10) organizations to obtain the feedback from their employees at various work levels. Five hypotheses were proposed and tested to find out factors (i.e., ICT usage, creativity, peer influence, management support and training) that influence effective learning in the context of an organization. in general, this study found that at the management level, factors such as work culture, organizational learning activities and leadership style can influence organizational approaches in promoting and building a learning organization. The outcomes from the survey further reveal that factors such as ICT utilization, training and creativity can directly influence employee's learning efforts. Interestingly, this study found no significant relationship between peer influence and employee's learning effort. The findings of this research inarguably will fill the present literature gap and also have various important managerial implications.